Corrosion-resistant alloy material for rail transit bridge system and preparation process of corrosion-resistant alloy material
Through microarc oxidation treatment and plasma spraying, combined with the sealing agent of carbon nanotube composite, the corrosion resistance and mechanical properties of magnesium-aluminum alloy materials for rail transit bridge systems are improved, and the corrosion resistance inadequate in the existing technology is solved. The problem of poor bonding with the coating.
Patent Information
- Application Number
- CN202411304719.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-19
- Publication Date
- 2024-12-31
AI Technical Summary
In the prior art, the corrosion resistance and hardness of the magnesium-aluminum alloy material used in rail transit bridge systems is insufficient, the coating and substrate bonding force are poor, the protection effect is poor, and the preparation process is complicated.
Microarc oxidation treatment is used to form a ceramic layer, metal film is sprayed with plasma spraying, and carbon nanotube composite is added to the sealing agent, and surface quality and adhesion are improved through ultraviolet light irradiation and heat treatment to form a corrosion-resistant alloy material.
It significantly improves the wear resistance, corrosion resistance and thermal stability of magnesium-aluminum alloy, enhances the bonding force between the ceramic layer and the metal film, and ensures high adhesion and chemical resistance of the alloy material.
Smart Images

Figure BDA0005048789110000081
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of alloy materials, and in particular discloses a corrosion-resistant alloy material for a rail transit bridge system and a preparation process thereof. Background Art
[0002] The alloy materials used in rail transit bridge systems need to have good processing performance, mechanical properties, corrosion resistance, and lightweight characteristics; magnesium-aluminum alloys have the characteristics of low density, high specific strength, large specific elastic modulus, good formability, and impact resistance, and are widely used;
[0003] However, the corrosion resistance and hardness of magnesium-aluminum alloys need to be improved. The existing technology commonly uses electroplating, surface ceramic modification, coating of protective coatings and other methods to modify the surface of magnesium-aluminum alloys, but there are still problems such as poor bonding between the coating and the substrate, insufficient protective effect, insufficient mechanical strength, and complex preparation process. In summary, it is of great significance to study an alloy material for rail transit bridge systems with good corrosion resistance, good mechanical properties, high surface quality of the protective layer and not easy to fall off, and its preparation process. Summary of the invention
[0004] The object of the present invention is to provide a corrosion-resistant alloy material for a rail transit bridge system and a preparation process thereof, so as to solve the problems raised in the prior art.
[0005] To achieve the above object, the present invention provides the following technical solutions: A preparation process of a corrosion-resistant alloy material for a rail transit bridge system: S1: pretreating the surface of a base metal, then placing it in an electrolyte, and performing micro-arc oxidation treatment to obtain an alloy material A having a ceramic layer on the surface;
[0006] S2: Y2O3 powder, Ni powder, α-Al2O3 powder, and TiB2 powder are taken and vibrated to obtain mixed metal powder; the mixed metal powder is sprayed onto the surface of alloy material A by plasma spraying, and heat-treated at 220-240°C for 30-60 minutes to obtain a metal film, which is alloy material B;
[0007] S3: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 8 to 12 m 2 / L, irradiate with λ=365nm, 250W ultraviolet light for 0.5-1h, heat to 70-75℃ and dry for 4-6h to obtain corrosion-resistant alloy material.
[0008] More optimally, the pretreatment includes the following steps: sandblasting and cleaning; the sandblasting material is 500-600 μm brown corundum, the sandblasting air pressure is 1-1.2 MPa, the sandblasting angle is 70-90°, the distance between the spray gun and the mold surface is 0.1-0.15 m, so that the surface roughness Ra is 10-15; cleaning: ultrasonic cleaning in anhydrous ethanol for 5-10 minutes.
[0009] More optimally, the pretreatment includes the following steps: sandblasting and cleaning; the sandblasting material is 500-600 μm brown corundum (Nanjing Bermuda Biotechnology Co., Ltd.), the sandblasting pressure is 1 MPa, the sandblasting angle is 70°, the distance between the spray gun and the mold surface is 0.13 m, the surface roughness Ra is 12, and ultrasonic cleaning is performed in anhydrous ethanol for 10 minutes.
[0010] More optimally, the electrolyte includes the following raw materials: Na2SiO3 10-12 g / L, KOH 1.5-2.0 g / L, NaF 0.5-1.0 g / L, Na3PO4 1.0-1.5 g / L.
[0011] More optimally, the electrolyte includes the following raw materials: Na2SiO3 10g / L, KOH 2.0g / L, NaF 0.8g / L, Na3PO4 1.2g / L.
[0012] More optimally, the parameters of the micro-arc oxidation treatment are: substrate pulse bias voltage is -100 to 500 V, pulse frequency is 200 to 250 Hz, positive pulse width is 20 to 25 μs, negative pulse width is 10 to 15 μs, and treatment time is 60 to 90 minutes.
[0013] More optimally, the ceramic layer has a thickness of 20 to 30 μm.
[0014] More optimally, the mixed metal powder includes the following raw materials, by mass percentage: 1-3% Y2O3 powder, 10-20% Ni powder, 30-40% α-Al2O3 powder, and the rest TiB2 powder; the plasma spraying method has a powder feeding rate of 40-60 g / min, a spraying speed of 15-25 mm / min, and a spraying distance of 80-100 mm.
[0015] More optimally, the plasma spraying method has a powder feeding rate of 50 g / min, a spraying speed of 20 mm / min, and a spraying distance of 100 mm.
[0016] More optimally, the thickness of the metal film is 30-45 μm.
[0017] More optimally, the sealing agent includes 10 to 15 parts of a carbon nanotube composite, 4 to 6 parts of a mercapto-containing siloxane copolymer, 0.01 to 0.02 parts of a photoinitiator (TPO), 0.01 to 0.02 parts of a thermal initiator (azobisisobutyronitrile), and 1000 parts of a solvent (dimethyl sulfoxide and water in a volume ratio of 1:1).
[0018] More optimally, the preparation of the carbon nanotube composite comprises the following steps: Step 1: taking carbon nanotubes, adding them to water and ethanol, stirring evenly, adding 3-aminopropyltriethoxysilane, heating to 40-60° C., stirring for 4-6 hours, filtering out the solid, and drying to obtain amino carbon nanotubes;
[0019] Step 2: Take the amino carbon nanotubes and add them into water, add 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide, stir evenly, add carboxymethyl chitosan and aminogabatrin, stir evenly, heat to 45-50°C, stir for 4-6 hours, filter the solid, wash and dry to obtain the carbon nanotube composite.
[0020] Preferably, the amino carbon nanotubes include the following raw materials, calculated by weight: 10 parts of carbon nanotubes, 0.5 to 1 part of 3-aminopropyltriethoxysilane;
[0021] The carbon nanotube composite comprises the following raw materials, calculated by weight: 2-3 parts of amino carbon nanotubes, 0.1-0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.2-0.4 parts of N-hydroxysuccinimide, 4-6 parts of carboxymethyl chitosan, and 1-2 parts of vigabatrin.
[0022] More optimally, the mercapto-containing siloxane copolymer is a (mercapto)methylsiloxane-dimethylsiloxane copolymer.
[0023] More optimally, the matrix metal is a magnesium-aluminum alloy, specifically comprising the following raw materials, by weight percentage: Al 25-30%, Fe 0.01-0.05%, Si 0.01-0.05%, Y0.1-0.2%, Zr 0.2-0.4%, Cu 1.0-2.0%, Mn 0.2-0.5%, and the rest is Mg.
[0024] Preferably, the matrix metal is a magnesium-aluminum alloy, specifically comprising the following raw materials, by weight percentage: Al 28%, Fe 0.04%, Si 0.03%, Y 0.1%, Zr 0.3%, Cu 1.5%, Mn 0.3%, and the rest is Mg.
[0025] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the base metal is a magnesium-aluminum alloy with low density, good formability, weldability and impact resistance; after the base metal surface is pretreated, micro-arc oxidation treatment is performed to obtain a ceramic layer; the ceramic layer has good bonding with the base metal, which can improve the wear resistance and corrosion resistance of the base metal surface on the one hand, and on the other hand, the surface ceramic layer generated by the micro-arc oxidation method has a certain roughness, which provides more contact area and anchoring points for the metal film layer sprayed by the plasma method in the next step, and enhances the adhesion between layers; the metal film layer includes a certain amount of Y2O3 powder, Ni powder, α-Al2O3 powder, and TiB2 powder, which enhance the surface corrosion resistance, hardness, wear resistance and thermal stability, and have good adhesion; the thickness of the ceramic layer and the metal film needs to be controlled, too high a thickness will lead to reduced bonding strength, too high internal stress will lead to cracks, and too low a thickness will lead to no obvious performance improvement;
[0026] After the metal film is sprayed, a sealing treatment is performed to eliminate small voids and cracks on the surface; a carbon nanotube composite is added to the sealing agent, specifically carbon nanotubes grafted with carboxymethyl chitosan containing double bonds; the carboxymethyl chitosan plays a role in corrosion inhibition and complexation, and strengthens the binding of the carbon nanotubes to the metal; the sealing agent also contains a (mercapto) methylsiloxane-dimethylsiloxane copolymer, which can reduce surface tension and improve surface chemical resistance; the carboxymethyl chitosan grafted on the carbon nanotubes is hydrophilic and can interact with the metal surface, which helps the carbon nanotubes to better penetrate into the pores and improve the sealing effect; under the action of a photoinitiator and a thermal initiator, the thiol group of the (mercapto) methylsiloxane-dimethylsiloxane copolymer reacts with the double bonds, and due to its hydrophobicity, it can diffuse and spread well on the surface of the alloy material, improve the corrosion resistance and hydrophobicity and other properties, and further improve the surface quality. DETAILED DESCRIPTION
[0027] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The following parts are by mass unless otherwise specified;
[0029] Example 1: S1: Take 10 parts of carbon nanotubes, add them to 50 parts of water and 50 parts of ethanol, stir evenly, add 0.8 parts of 3-aminopropyltriethoxysilane, heat to 50°C, stir for 5h, filter out the solid, and dry to obtain amino carbon nanotubes;
[0030] S2: Take 3 parts of amino carbon nanotubes and add them to 70 parts of water, add 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.3 parts of N-hydroxysuccinimide, stir evenly, add 5 parts of carboxymethyl chitosan and 1.5 parts of aminohexanoic acid, stir evenly, heat to 50°C, stir for 5 hours, filter the solid, wash and dry to obtain a carbon nanotube composite;
[0031] S3: Take 12 parts of carbon nanotube composite, 5 parts of (mercapto) methylsiloxane-dimethylsiloxane copolymer, 0.01 parts of photoinitiator, 0.01 parts of thermal initiator, and 1000 parts of solvent and mix them evenly to obtain a sealing agent;
[0032] S4: pre-treating the surface of the base metal, and then placing it in an electrolyte for micro-arc oxidation treatment; obtaining an alloy material A with a 25 μm ceramic layer generated on the surface; the parameters of the micro-arc oxidation treatment are: base pulse bias voltage of 400 V, pulse frequency of 200 Hz, positive pulse width of 22 μs, negative pulse width of 12 μs, and treatment time of 65 minutes;
[0033] S5: Take 2 parts of yttrium oxide powder, 18 parts of nickel powder, 35 parts of α-Al2O3 powder, and 45 parts of TiB2 powder, use SPEX (8000DMixer / Mill) to mix and granulate for 15 minutes under simple horizontal vibration to obtain mixed metal powder; use plasma spraying to spray the mixed metal powder onto the surface of alloy material A, and heat it at 240°C for 30 minutes to obtain a metal film with a thickness of 35μm, which is alloy material B;
[0034] S6: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 10m 2 / L, irradiate with λ=365nm, 250W ultraviolet light for 1h, heat to 75℃ and dry for 5h to obtain corrosion-resistant alloy material.
[0035] Example 2: S1: Take 10 parts of carbon nanotubes, add them to 50 parts of water and 50 parts of ethanol, stir evenly, add 0.8 parts of 3-aminopropyltriethoxysilane, heat to 50°C, stir for 5h, filter out the solid, and dry to obtain amino carbon nanotubes;
[0036] S2: Take 2 parts of amino carbon nanotubes and add them to 70 parts of water, add 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.3 parts of N-hydroxysuccinimide, stir evenly, add 4 parts of carboxymethyl chitosan and 1 part of aminohexanoic acid, stir evenly, heat to 50°C, stir for 5 hours, filter the solid, wash and dry to obtain a carbon nanotube composite;
[0037] S3: Take 12 parts of carbon nanotube composite, 5 parts of (mercapto) methylsiloxane-dimethylsiloxane copolymer, 0.01 parts of photoinitiator, 0.01 parts of thermal initiator, and 1000 parts of solvent and mix them evenly to obtain a sealing agent;
[0038] S4: pre-treating the surface of the base metal, and then placing it in an electrolyte for micro-arc oxidation treatment; obtaining an alloy material A with a 25 μm ceramic layer generated on the surface; the parameters of the micro-arc oxidation treatment are: base pulse bias voltage of 400 V, pulse frequency of 200 Hz, positive pulse width of 22 μs, negative pulse width of 12 μs, and treatment time of 65 minutes;
[0039] S5: Take 1 part of yttrium oxide powder, 15 parts of nickel powder, 39 parts of α-Al2O3 powder, and 45 parts of TiB2 powder, use SPEX (8000DMixer / Mill) to mix and granulate for 15 minutes under simple horizontal vibration to obtain mixed metal powder; use plasma spraying method to spray the mixed metal powder onto the surface of alloy material A, and heat it at 240℃ for 30 minutes to obtain a metal film with a thickness of 35μm, which is alloy material B;
[0040] S6: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 10m 2 / L, irradiate with λ=365nm, 250W ultraviolet light for 1h, heat to 75℃ and dry for 5h to obtain corrosion-resistant alloy material.
[0041] Example 3: S1: Take 10 parts of carbon nanotubes, add them to 50 parts of water and 50 parts of ethanol, stir evenly, add 0.8 parts of 3-aminopropyltriethoxysilane, heat to 50°C, stir for 5 hours, filter out the solid, and dry to obtain amino carbon nanotubes;
[0042] S2: Take 3 parts of amino carbon nanotubes and add them to 70 parts of water, add 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.3 parts of N-hydroxysuccinimide, stir evenly, add 6 parts of carboxymethyl chitosan and 2 parts of aminohexanoic acid, stir evenly, heat to 50°C, stir for 5 hours, filter the solid, wash and dry to obtain a carbon nanotube composite;
[0043] S3: Take 12 parts of carbon nanotube composite, 5 parts of (mercapto) methylsiloxane-dimethylsiloxane copolymer, 0.01 parts of photoinitiator, 0.01 parts of thermal initiator, and 1000 parts of solvent and mix them evenly to obtain a sealing agent;
[0044] S4: pre-treating the surface of the base metal, and then placing it in an electrolyte for micro-arc oxidation treatment; obtaining an alloy material A with a 25 μm ceramic layer generated on the surface; the parameters of the micro-arc oxidation treatment are: base pulse bias voltage of 400 V, pulse frequency of 200 Hz, positive pulse width of 22 μs, negative pulse width of 12 μs, and treatment time of 65 minutes;
[0045] S5: Take 3 parts of yttrium oxide powder, 12 parts of nickel powder, 30 parts of α-Al2O3 powder, and 55 parts of TiB2 powder, use SPEX (8000DMixer / Mill) to mix and granulate for 15 minutes under simple horizontal vibration to obtain mixed metal powder; use plasma spraying to spray the mixed metal powder onto the surface of alloy material A, and heat it at 240°C for 30 minutes to obtain a metal film with a thickness of 35μm, which is alloy material B;
[0046] S6: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 10m 2 / L, irradiate with λ=365nm, 250W ultraviolet light for 1h, heat to 75℃ and dry for 5h to obtain corrosion-resistant alloy material.
[0047] Comparative Example 1 (the thickness of the ceramic layer and the metal film is changed, and the other method steps are consistent with Example 1): S1: Take 10 parts of carbon nanotubes, add them to 50 parts of water and 50 parts of ethanol, stir evenly, add 0.8 parts of 3-aminopropyltriethoxysilane, heat to 50°C, stir for 5h, filter and take the solid, and dry to obtain amino carbon nanotubes;
[0048] S2: Take 3 parts of amino carbon nanotubes and add them to 70 parts of water, add 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.3 parts of N-hydroxysuccinimide, stir evenly, add 5 parts of carboxymethyl chitosan and 1.5 parts of aminohexanoic acid, stir evenly, heat to 50°C, stir for 5 hours, filter the solid, wash and dry to obtain a carbon nanotube composite;
[0049] S3: Take 12 parts of carbon nanotube composite, 5 parts of (mercapto) methylsiloxane-dimethylsiloxane copolymer, 0.01 parts of photoinitiator, 0.01 parts of thermal initiator, and 1000 parts of solvent and mix them evenly to obtain a sealing agent;
[0050] S4: pre-treating the surface of the base metal, and then placing it in an electrolyte for micro-arc oxidation treatment; obtaining an alloy material A having a 35 μm ceramic layer generated on the surface;
[0051] S5: Take 2 parts of yttrium oxide powder, 18 parts of nickel powder, 35 parts of α-Al2O3 powder, and 45 parts of TiB2 powder, use SPEX (8000DMixer / Mill) to mix and granulate for 15 minutes under simple horizontal vibration to obtain mixed metal powder; use plasma spraying to spray the mixed metal powder onto the surface of alloy material A, and heat it at 240°C for 30 minutes to obtain a metal film with a thickness of 25μm, which is alloy material B;
[0052] S6: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 10m 2 / L, irradiate with λ=365nm, 250W ultraviolet light for 1h, heat to 75℃ and dry for 5h to obtain corrosion-resistant alloy material.
[0053] Comparative Example 2 (the thickness of the ceramic layer and the metal film is changed, and the other method steps are consistent with Example 1): S1: Take 10 parts of carbon nanotubes, add them to 50 parts of water and 50 parts of ethanol, stir evenly, add 0.8 parts of 3-aminopropyltriethoxysilane, heat to 50°C, stir for 5h, filter and take out the solid, and dry to obtain amino carbon nanotubes;
[0054] S2: Take 3 parts of amino carbon nanotubes and add them to 70 parts of water, add 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.3 parts of N-hydroxysuccinimide, stir evenly, add 5 parts of carboxymethyl chitosan and 1.5 parts of aminohexanoic acid, stir evenly, heat to 50°C, stir for 5 hours, filter the solid, wash and dry to obtain a carbon nanotube composite;
[0055] S3: Take 12 parts of carbon nanotube composite, 5 parts of (mercapto) methylsiloxane-dimethylsiloxane copolymer, 0.01 parts of photoinitiator, 0.01 parts of thermal initiator, and 1000 parts of solvent and mix them evenly to obtain a sealing agent;
[0056] S4: pre-treating the surface of the base metal, and then placing it in an electrolyte for micro-arc oxidation treatment; obtaining an alloy material A having a ceramic layer of 15 μm generated on the surface;
[0057] S5: Take 2 parts of yttrium oxide powder, 18 parts of nickel powder, 35 parts of α-Al2O3 powder, and 45 parts of TiB2 powder, use SPEX (8000DMixer / Mill) to mix and granulate for 15 minutes under simple horizontal vibration to obtain mixed metal powder; use plasma spraying to spray the mixed metal powder onto the surface of alloy material A, and heat it at 240°C for 30 minutes to obtain a metal film with a thickness of 45μm, which is alloy material B;
[0058] S6: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 10m 2 / L, irradiate with λ=365nm, 250W ultraviolet light for 1h, heat to 75℃ and dry for 5h to obtain corrosion-resistant alloy material.
[0059] Comparative Example 3 (the preparation method of the sealing agent is changed, and the other method steps are consistent with Example 1): S1: Take 10 parts of carbon nanotubes, add 50 parts of water and 50 parts of ethanol, stir evenly, add 0.8 parts of 3-aminopropyltriethoxysilane, heat to 50° C., stir for 5 hours, filter and take the solid, and dry to obtain amino carbon nanotubes;
[0060] S2: Take 3 parts of amino carbon nanotubes and add them to 70 parts of water, add 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.3 parts of N-hydroxysuccinimide, stir evenly, add 5 parts of carboxymethyl chitosan and 1.5 parts of aminohexanoic acid, stir evenly, heat to 50°C, stir for 5 hours, filter the solid, wash and dry to obtain a carbon nanotube composite;
[0061] S3: taking 12 parts of the carbon nanotube composite and 1000 parts of the solvent and mixing them evenly to obtain a sealing agent;
[0062] S4: pre-treating the surface of the base metal, and then placing it in an electrolyte for micro-arc oxidation treatment; obtaining an alloy material A with a 25 μm ceramic layer generated on the surface; the parameters of the micro-arc oxidation treatment are: base pulse bias voltage of 400 V, pulse frequency of 200 Hz, positive pulse width of 22 μs, negative pulse width of 12 μs, and treatment time of 65 minutes;
[0063] S5: Take 2 parts of yttrium oxide powder, 18 parts of nickel powder, 35 parts of α-Al2O3 powder, and 45 parts of TiB2 powder, use SPEX (8000DMixer / Mill) to mix and granulate for 15 minutes under simple horizontal vibration to obtain mixed metal powder; use plasma spraying to spray the mixed metal powder onto the surface of alloy material A, and heat it at 240°C for 30 minutes to obtain a metal film with a thickness of 35μm, which is alloy material B;
[0064] S6: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 10m 2 / L, irradiate with λ=365nm, 250W ultraviolet light for 1h, heat to 75℃ and dry for 5h to obtain corrosion-resistant alloy material.
[0065] Comparative Example 4 (the preparation method of the corrosion-resistant alloy material is changed, and the other method steps are consistent with Example 1): S1: Take 10 parts of carbon nanotubes, add them to 50 parts of water and 50 parts of ethanol, stir evenly, add 0.8 parts of 3-aminopropyltriethoxysilane, heat to 50°C, stir for 5h, filter and take out the solid, and dry to obtain amino carbon nanotubes;
[0066] S2: Take 3 parts of amino carbon nanotubes and add them to 70 parts of water, add 0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide and 0.3 parts of N-hydroxysuccinimide, stir evenly, add 5 parts of carboxymethyl chitosan and 1.5 parts of aminohexanoic acid, stir evenly, heat to 50°C, stir for 5 hours, filter the solid, wash and dry to obtain a carbon nanotube composite;
[0067] S3: taking 12 parts of carbon nanotube composite, 5 parts of (mercapto) methylsiloxane-dimethylsiloxane copolymer, and 1000 parts of solvent and mixing them evenly to obtain a sealing agent;
[0068] S4: pre-treating the surface of the base metal, and then placing it in an electrolyte for micro-arc oxidation treatment; obtaining an alloy material A with a 25 μm ceramic layer generated on the surface; the parameters of the micro-arc oxidation treatment are: base pulse bias voltage of 400 V, pulse frequency of 200 Hz, positive pulse width of 22 μs, negative pulse width of 12 μs, and treatment time of 65 minutes;
[0069] S5: Take 2 parts of yttrium oxide powder, 18 parts of nickel powder, 35 parts of α-Al2O3 powder, and 45 parts of TiB2 powder, use SPEX (8000DMixer / Mill) to mix and granulate for 15 minutes under simple horizontal vibration to obtain mixed metal powder; use plasma spraying to spray the mixed metal powder onto the surface of alloy material A, and heat it at 240°C for 30 minutes to obtain a metal film with a thickness of 35μm, which is alloy material B;
[0070] S6: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 10m 2 / L, dry and obtain corrosion-resistant alloy material.
[0071] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); yttrium oxide powder (50 μm, Ningbo Yumu New Materials Co., Ltd.); nickel powder (ML-Ni-N50, Zhejiang Manli Nano Technology Co., Ltd.); α-Al2O3 powder (YM-Al2O3-W50, Ningbo Yumu New Materials Co., Ltd.); TiB2 powder (YM-TiB2-N50, Ningbo Yumu New Materials Co., Ltd.); carbon nanotubes (T19281, Shanghai Yuanye); 3-aminopropyltriethoxysilane Alkane (CAS: 919-30-2); 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC, CAS: 25952-53-8); N-hydroxysuccinimide (CAS: 6066-82-6); carboxymethyl chitosan (S30948, Shanghai Yuanye); aminogalic acid (CAS: 60643-86-9); (mercapto)methylsiloxane-dimethylsiloxane copolymer (T22821, Shanghai Yuanye); dimethyl sulfoxide (CAS: 67-68-5); azobisisobutyronitrile (CAS: 78-67-1); photoinitiator TPO (CAS: 75980-60-8).
[0072] Experiment: Take the corrosion-resistant alloy materials prepared in Examples 1 to 3 and Comparative Examples 1 to 4; (1) with reference to GB / T 12967.3-2008, in a YWX / Q-250B salt spray corrosion chamber, a salt spray test was carried out by using a hanging piece continuous spraying method, with a NaCl concentration of 5%, a pH of 3, a temperature of 50°C, a salt spray corrosion time of 48h, and a maximum corrosion depth tested; (2) with reference to GB / T 15114-2009, the hardness was tested; the specific data are shown in the table below;
[0073]
[0074] Conclusion: Comparative Examples 1 and 2 changed the thickness of the ceramic layer and the metal film, both resulting in a decrease in performance, which shows that controlling the thickness is of great significance; Comparative Example 3 changed the preparation method of the sealing agent, did not introduce the (mercapto)methylsiloxane-dimethylsiloxane copolymer, and the performance decreased; Comparative Example 4 did not add photoinitiator and thermal initiator, sprayed the sealing agent and then directly dried to obtain a corrosion-resistant alloy material, and the performance was not as good as the embodiment; in summary, the corrosion-resistant alloy material prepared by the present invention has good corrosion resistance and mechanical properties.
[0075] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.
Claims
1. A preparation process of a corrosion-resistant alloy material for a rail transit bridge system, characterized in that: S1: pre-treating the surface of the base metal, then placing it in an electrolyte and performing micro-arc oxidation treatment to obtain an alloy material A with a ceramic layer on the surface; S2: Y2O3 powder, Ni powder, α-Al2O3 powder, and TiB2 powder are taken and mixed by vibration to obtain mixed metal powder; the mixed metal powder is sprayed onto the surface of alloy material A by plasma spraying, and heat-treated to obtain a metal film, which is alloy material B; S3: Spray the sealing agent onto the surface of alloy material B, with a spraying amount of 8 to 12 m 2 / L, ultraviolet light exposure for 0.5 to 1h, heating and drying for 4 to 6h to obtain corrosion-resistant alloy material.
2. The preparation process of a corrosion-resistant alloy material for a rail transit bridge system according to claim 1 is characterized in that: The electrolyte includes the following raw materials: Na2SiO3 10-12 g / L, KOH 1.5-2.0 g / L, NaF 0.5-1.0 g / L, Na3PO4 1.0-1.5 g / L; The parameters of the micro-arc oxidation treatment are: substrate pulse bias voltage is -100 to 500 V, pulse frequency is 200 to 250 Hz, positive pulse width is 20 to 25 μs, negative pulse width is 10 to 15 μs, and treatment time is 60 to 90 minutes.
3. The preparation process of the corrosion-resistant alloy material for rail transit bridge system according to claim 1 is characterized in that: The thickness of the ceramic layer is 20-30 μm; the thickness of the metal film is 30-45 μm.
4. The preparation process of a corrosion-resistant alloy material for a rail transit bridge system according to claim 1 is characterized in that: The mixed metal powder includes the following raw materials, by mass percentage: 1-3% Y2O3 powder, 10-20% Ni powder, 30-40% α-Al2O3 powder, and the rest is TiB2 powder; the powder feeding rate of the plasma spraying method is 40-60g / min, the spraying speed is 15-25mm / min, and the spraying distance is 80-100mm.
5. The preparation process of the corrosion-resistant alloy material for rail transit bridge system according to claim 1 is characterized in that: The sealing agent comprises the following raw materials, calculated by weight: 10 to 15 parts of carbon nanotube composite, 4 to 6 parts of mercapto-containing siloxane copolymer, 0.01 to 0.02 parts of photoinitiator, 0.01 to 0.02 parts of thermal initiator, and 1000 parts of solvent.
6. The process for preparing a corrosion-resistant alloy material for a rail transit bridge system according to claim 5, characterized in that: The preparation of the carbon nanotube composite comprises the following steps: Step 1: taking carbon nanotubes, adding them to water and ethanol, stirring them evenly, adding 3-aminopropyltriethoxysilane, heating them to 40-60° C., stirring them for 4-6 hours, filtering out the solids, and drying them to obtain amino carbon nanotubes; Step 2: Take the amino carbon nanotubes and add them into water, add 1-ethyl-(3-dimethylaminopropyl) carbodiimide and N-hydroxysuccinimide, stir evenly, add carboxymethyl chitosan and aminogabatrin, stir evenly, heat to 45-50°C, stir for 4-6 hours, filter the solid, wash and dry to obtain the carbon nanotube composite.
7. The process for preparing a corrosion-resistant alloy material for a rail transit bridge system according to claim 6, characterized in that: The amino carbon nanotubes include the following raw materials, calculated by weight: 10 parts of carbon nanotubes, 0.5 to 1 part of 3-aminopropyltriethoxysilane; The carbon nanotube composite comprises the following raw materials, calculated by weight: 2-3 parts of amino carbon nanotubes, 0.1-0.2 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide, 0.2-0.4 parts of N-hydroxysuccinimide, 4-6 parts of carboxymethyl chitosan, and 1-2 parts of vigabatrin.
8. The process for preparing a corrosion-resistant alloy material for a rail transit bridge system according to claim 6 is characterized in that: The mercapto-containing siloxane copolymer is a (mercapto)methylsiloxane-dimethylsiloxane copolymer.
9. The process for preparing a corrosion-resistant alloy material for a rail transit bridge system according to claim 1, characterized in that: The matrix metal is a magnesium-aluminum alloy, specifically comprising the following raw materials, by weight percentage: Al 25-30%, Fe 0.01-0.05%, Si 0.01-0.05%, Y 0.1-0.2%, Zr 0.2-0.4%, Cu 1.0-2.0%, Mn 0.2-0.5%, and the rest is Mg.
10. The corrosion-resistant alloy material prepared according to the preparation process of the corrosion-resistant alloy material for rail transit bridge system according to any one of claims 1 to 9.
